Sistema web para el seguimiento y control de los procesos de crianza de cobayas de la granja familiar Quishpe - Quishpe Proaño, Elvis Fabian (2024)
The raising of guinea pigs constitutes an important source of income for rural communities in the Andean region of Latin America. However, producers face challenges in managing and processing key information related to the reproduction, weights, and causes of mortality of guinea pigs, which is usually recorded manually in spreadsheets or on paper, making analysis and decision-making difficult. Recognizing the need to implement technological solutions in animal husbandry, the present research focused on the development of a web system using the Laravel framework for tracking and controlling the guinea pig breeding processes at the Quishpe family farm. This web system was developed following the agile Extreme Programming methodology, which allowed for an adaptable approach and constant incorporation of user feedback. Visual Studio Code was used for coding, while MySQL Workbench was employed for database management. The selected programming languages included HTML, JavaScript, PHP, and CSS, providing a comprehensive solution that encompasses the creation of attractive and responsive user interfaces, the implementation of business logic, data management, and integration with the database. The developed web system allows for efficient control and monitoring of guinea pig reproduction, management of food resources, and a clear overview of sales and mortality of this species. Thanks to this technological solution, the producer can visualize profits and losses in real-time, as well as select the best specimens based on the provided information, ensuring business continuity and compliance with desired weight standards and characteristics. Furthermore, comprehensive unit tests were carried out to validate the correct functioning of the web system, ensuring that it met the specific requirements and needs of the farm.